Greater performance impairment of black runners than white runners when running in hypoxia - Santos-Concejero, J.; Tucker, R.; Myburgh, K. H.; Essen-Gustavsson, B.; Kohn, T. A. (International Journal of Sports Medicine, 2014)
This study aimed to compare the response of performance-matched black and white runners during maximal and sub-maximal running in normoxic and hypoxic conditions. 14 well-trained runners (8 black, 6 white) performed 2 incremental maximal exercise tests and 2 fatigue resistance tests at 21% O2 (normoxia) or 14% O2 (hypoxia). Respiratory parameters, heart rate (HR), lactate concentration ([La-]) as well as arterial saturation (SpO2) were measured. Enzyme activities and myosin heavy chain content (MHC) were also measured. White runners reached a significantly greater peak treadmill speed and a higher HRmax than black runners in hypoxia (p<0.05). Additionally, White runners achieved a greater time to fatigue than black runners (p<0.05), with black runners displaying a greater decline in performance in hypoxia compared to normoxia (20.3% vs. 13.4%, black vs. white, respectively). However, black runners presented lower [La-] and higher SpO2 than white runners in hypoxia (p<0.05). Black runners had a higher proportion of MHC IIa and higher lactate dehydrogenase activity (p<0.05). The greater performance impairment observed in black runners in hypoxia suggests a greater performance sensitivity to this condition, despite the maintenance of physiological variables such as SpO2 and [La - ] within a smaller range than white runners.